A study of the perceptions of race and experience of prejudice in Grade Four learners at a Cape Town primary school - West, Verusha (Department of Social Development, 2014)
The researcher is a social worker at a primary school in Cape Town. This school was previously reserved for white children during the apartheid era, but now provides education for a multi-racial group of children, who are predominantly of mixed race. The researcher became aware that incidents of bullying and learner conflict in the school took on a racial flavour at times, but that there was a tendency to deny that race was a difficulty with which the children struggled. She embarked on this research in order to examine the views and experiences of these learners with regards to race and prejudice. The researcher employed a qualitative research design and made use of a number of focus groups to gather data. These groups were run with Grade Four learners in the primary school, and explored their understanding of race, as well as their views of people from the different races that they identified. They were also asked about their own experiences of being treated in a negatively prejudiced way. The results show that while the children tended to be reluctant at first to speak about issues of race, many of them had very strong views about their own and other groups. Some children showed very strong prejudice towards people from out-groups, while others displayed strong own-group preference, with little out-group prejudice. On the whole, participants were very reluctant to speak of experiences of negative prejudice shown towards them. The report is concluded with some recommendations for further study into this area of South African children, race and prejudice, as well as some recommendations to the school where the study was conducted. KEYWORDS: Racism, Prejudice, Desegregated Schooling, Children, Post Apartheid Education, Contact Hypothesis, Social Identity Development Theory.